Developing a Ceramic Construction Product under Bioclimatic and Sustainable Architecture Principles (2020)
The role of facades is fundamental to determine the energy performance of a building. According to the properties of construction elements, the heat transfer towards the interior can be strategically controlled to avoid increases in energy demand by the cooling system. The development of insulating products can solve this problem. In Norte de Santander, Colombia, the thriving clay industry is based on raw material quality. This paper designs and validates the thermal behavior of two proposed ventilated bricks, called eco Design. The thermal validation was fulfilled using the ANSYS R16 software to simulate the transfer and heat fluxes according to shape and material. The best performance was achieved by an extruded process to determine the mechanical properties on a laboratory scale in different mixtures with technological additives. The results show that the ventilated air chamber can reduce the inner surface temperature up to 45.5 °F. Nevertheless, the strength of these new products is considerably reduced compared to traditional multi-perforated brick.